UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL TPS BERBANTUAN MEDIA DIGIMATH FUN PADA SISWA KELAS V SD - Cindy Fatika Amelia; Elly’s Mersina Mursidik; Rissa Prima Kurniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the improvement of Mathematics learning outcomes through the application of the TPS type Cooperative learning model assisted by Digimath Fun media. This study is a classroom action research (CAR) conducted in two cycles. The subjects were 16 fifth-grade students of SDN Grobogan 02. Each cycle consists of four stages, namely planning, action implementation, observation, and reflection. Data collection techniques used include observation, testing, and documentation. The instruments used include teaching modules, teacher activity observation sheets, student activity observation sheets, pre-test and post-test questions for cycles I and II, and also documentation during the learning process. The results of the study indicate that the application of the TPS type Cooperative learning model assisted by Digimath Fun media can improve students' Mathematics learning outcomes. In the pre-cycle, student learning completeness only reached 25%, increased to 56.75% in cycle I, and reached 93.75% in cycle II. In addition, teacher and student activities in the learning process also increased at each meeting. Thus, it can be concluded that the TPS type Cooperative learning model assisted by Digimath Fun media is effective in improving the Mathematics learning outcomes of fifth grade students at SDN Grobogan 02, Jiwan, Madiun Regency.